Rapamycin Ameliorates Neuropathic Pain by Activating Autophagy and Inhibiting Interleukin-1β in the Rat Spinal Cord - 冯涛 殷琴 翁泽林 张建成 王昆锋 袁世荧 程伟 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Autophagy acts as an important homoeostatic mechanism by degradation of cytosolic con- stituents and plays roles in many physiological processes. Recent studies demonstrated that autophagy can also regulate the production and secretion of the proinflammatory cytokine interleukin-1β （IL-1β）, which plays a critical role in the development and maintenance ofneuropathic pain. In the present study, the paw withdrawal threshold （PWT） and paw withdrawal latency （PWL） were significantly decreased after spinal nerve ligation （SNL）, and the changes were accompanied by inhibited autophagy in the spi- nal microglia and increased mR.NA and protein levels of IL-1β in the ipsilateral spinal cord. We then investigated the antinociceptive effect of rapamycin, a widely used autopahgy inducer, on SNL-induced neuropathic pain in rats and found that treatment with intrathecal rapamycin significantly attenuated the mechanical allodynia and thermal hyperalgesia. Moreover, rapamycin significantly enhanced autophagy in the spinal microglia, whereas it reduced the mRNA and protein levels of IL-1β in the ipsilateral spinal cord. Our results showed that rapamycin could ameliorate neuropathic pain by activating autophagy and inhibiting IL-1β in the spinal cord.